2018
DOI: 10.1371/journal.pone.0200614
|View full text |Cite
|
Sign up to set email alerts
|

Wishes and needs of community-dwelling older persons concerning general practice: A qualitative study

Abstract: IntroductionCommunity-dwelling older persons often experience hindering health complaints that disturb daily activities. If general practitioners (GPs) are unaware of such complaints, this could lead to a mismatch in provided care and needed or expected care. In this qualitative study with community-dwelling older persons we investigated how older persons experience hindering health complaints, how they deal with them, and what they expect from their GP.MethodsParticipants (aged ≥80 years) with pain and/or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Older patients thought effective communication should occur between health professionals situated in hospitals and those in community settings, however these expectations were often not met. Similarly, older patients expected their PCPs to be well informed about their updated medications, and they also expected them to communicate regularly with their medical specialists; this communication did not always occur 88 .…”
Section: Discussionmentioning
confidence: 99%
“…Older patients thought effective communication should occur between health professionals situated in hospitals and those in community settings, however these expectations were often not met. Similarly, older patients expected their PCPs to be well informed about their updated medications, and they also expected them to communicate regularly with their medical specialists; this communication did not always occur 88 .…”
Section: Discussionmentioning
confidence: 99%
“…For this topic, researchers (MvF, SP) worked together with the Regional Advisory Board of Older Persons [Ouderenberaad Zuid Holland-Noord] in the city of Leiden. The Regional Advisory Board of Older Persons is a client panel of 15 older persons (aged 60-90 years) who reflect on research proposals/results, housing, and healthcare policy in the Leiden area [26]. In 2017, a participative research on "Vitality and living independently" in the region was conducted.…”
Section: Leiden: Setting Participants and Methodsmentioning
confidence: 99%
“…Those participants who had already taken action often suggested that they would most likely need additional guidance from a general practice professional as they grew older. This expectation is supported by research showing that patient involvement changes with health status [4,18,20]. Professionals at general practices should be aware of these differences; some older patients are fully capable of organizing healthcare themselves, while others may rely on the initiative of their GP or practice nurse.…”
Section: Comparison With Literaturementioning
confidence: 98%
“…In most general practices in the Netherlands a practice nurse works with patients with chronic conditions and/or with older persons. An earlier study showed that older persons value the practice nurse [20], and a good relationship with their healthcare professional has been shown to encourage the open discussion of health problems [21,22]. This opens up possibilities for reflection and discussion on health and wellbeing with older persons, with an important role for the practice nurse.…”
Section: Comparison With Literaturementioning
confidence: 98%
See 1 more Smart Citation